From 3g to LTE: the feasibility of the transition for Zimbabwe mobile operators - Magadzire, Artwell (Midlands State University, 2015)
Mobile telecoms industry has become a key element of productivity across economies and societies worldwide. The rigorous demand for delivery of services of uncompromising quality in the highly competitive cellular industry has challenged the operators to constantly upgrade their networks. In Zimbabwe we have witnessed a significant transformation within this sector because of the impact it has on the economy with LTE being the latest technology to be considered by most mobile operators. While LTE is the fastest-growing cellular technology in history in terms of subscription-number growth, it is still very much a new technology both in terms of the total number of subscriptions and also the maturity of the service proposition. This report aims at researching on the feasibility for Zimbabwean operators to migrate from 3G to 4G LTE by analyzing the current state of the mobile telecom industry in Zimbabwe.